Uma proposta de modelo regional para mensurar os impactos de políticas nacionais em uma região: uma aplicação para o Ceará - Osterno, Isadora Gonçalves Costa (2022)
There is a recent research effort that suggests that modern macroeconomic analysis tools should be used to analyze regional issues. Rickman (2010) propose that macroeconometric treatment based on models DSGE and VAR global or restricted, can contribute with quick answers and empirical evidence on the inherent problems of the regional economics. This article builds an empirical analysis methodology for this purpose, which one we call SAMBA+REG. The idea is to build a theoretical instrument that brings together macroeconomic elements extracted from the model SAMBA, but that adds regional elements. Simulations with scal and monetary shocks on a parameterized economy for Ceará were implement and the results are compatible with the literature and reinforce the potential of this model. The SAMBA+REG it is capable of providing support not only for simulating the effects of economic policies by the Central Government on the Ceará economy, but it can also shed light on a list of alternatives for the State Government to respond adequately to these policies. The work shows that the model, in addition to bringing good empirical results, also has theoretical robustness, checked via identication tests.